Necrotizing enterocolitis associated Klebsiella pneumoniae sepsis - Thomas, Jessy (International Journal of Contemporary Pediatrics, 2023)
Necrotizing enterocolitis (NEC) is a common multifactorial illness of the gastrointestinal tract with life threatening complications affecting mostly premature infants. NEC associated sepsis often cause high mortality and severe morbidity in newborns. The present paper reports a severe form of necrotizing enterocolitis in a preterm infant with Klebsiella pneumoniae sepsis.